Pengelolaan Lingkungan dalam Rangka Mengantisipasi Perkembangan Hama Belalang Nomadacris succincta Linnaeus (Orthoptera: Acrididae) - Sri Suharni Siwi; Trisnaningsih Trisnaningsih; Harnoto Harnoto (Jurnal Perlindungan Tanaman Indonesia, 2005)
Swarming grasshopper Nomadacris succincta (Linnaeus), sinonim: Patanga succincta (L.) was one of the dominant species attacked corn and soybean plantations at Jeneponto District, South Sulawesi in early 2005. The species has been identified for a long time occurred in that environment, although has never been reported before as pest of farmer's crops. For a basis of the capability in controlling the swarm grasshopper in the field, changed of increasing population hould be monitored regularly to prevent future outbreak. Information on taxonomic and ecology research of N. succincta are needed for environmental management efforts, such as change in morphology, physiology and behavior, change in host's preferences of gregarious adult, and environmental conditions i.e. climate, cultural techniques, and the death of natural enemies in the field.